Retroperitoneal pararenal castleman’s disease: a case report - Shrestha, S; Nepal, U; Lamichhane, N; Chhetri, P (Journal of Pathology of Nepal, 2013)
Castleman’s diseas is a rare lymphoproliferative disorder of unknown etiology. We report a 28 years old woman with solitary Castleman’s disease in the left pararenal space. This case was diagnosed preoperatively as renal cell carcinoma. The patient underwent a radical nephrectomy with dissection of pararenal mass. Histopathological examination of the surgically resected specimen showed the hyaline vascular type of Castleman’s disease. A preoperative diagnosis of Castleman’s disease is difficult; therefore, a surgical resection and histopathological evaluation can provide an accurate diagnosis of tumor. Taking this case into consideration, we suggest that Castleman’s disease should be included in the differential diagnosis of renal tumors. DOI: http://dx.doi.org/10.3126/jpn.v3i6.9004 Journal of Pathology of Nepal (2013) Vol. 3, 509-511